Terroirizing North Sea Cheese - Ostrowski, Kasper (STS Encounters, 2023)
This paper investigates the construction of the geographical claim that “the cheese has terroir”. Drawing on food-centered science and technology studies and on actor-network theory, I first propose terroirizing – a verbal noun for enacting terroir – as an analytic device in the exploration of how the origins and history of food are made tangible and how place and imaginaries are invoked to bind and fasten products and produce within specific geographical and sociocultural settings. Terroirizing, I argue, is a valuable analytic device for investigating enactments of place and the practice of terroir in regard to food and foodstuffs. The paper goes on to investigate the geographical claims promoted by a Danish dairy in order to terroirize a cheese and thus to advance a particular coastal place-specificity in a Danish foodscape with few strong affiliations with geographical claims. The terroirizing of Thise Dairy’s North Sea Cheese reveals that terroir and place are heterogenous constructs which are dependent not just on microclimate or measurable ecosystems, but also on the construction and circulation of specific imagery and materials. I demonstrate how cheese wrappings, advertisements, the North Sea itself, a ventilation technology, aerosols (sea-spray particles), and salt crystals are all brought together to form an assemblage – a cheese with a Nordic coastal terroir.